Data og repræsentativitet i ordbogsarbejdet - Hovmark, Henrik (Nordiske Studier i Leksikografi, 2012)
Nowadays, lexicography is closely associated with information technology and language technology tools. However, until fairly recently lexicography was based on traditional printing and collections of paper slips. Taking a description of the working processes in lexicographic work based on collections of paper slips, I discuss the relations between empirical data, work flow and final product in lexicography in general. I focus on the question of representativeness: When is a collection of paper slips representative? How and to what extent is it possible to make generalizations based on data which is highly qualitative? I point to the fact that any kind of data, text corpora as well as collections of paper slips, is the outcome of a selection and should be scrutinized critically by lexicographers.